Overview of Maternal Education Level and Family Income Among Stunting Children Under 5 Years Old at Puskesmas Parongpong Workplace In 2019 - Kelendonu, Cheryl Ginny B.; Djula, Sapti H. Widyarti (8ISC Abstract Proceedings, 2022)
Stunting is one of the nutritional problems where the presence of disorders in children's height is lower than the height of children at their age. The socioeconomic status of parents is one of the indirect causes of stunting. Some factors of parents are income and education. Mother plays an important role in the growth and development of a child. The purpose of this study was to describe the level of income and education of mothers who have stunted children under five years. The design of this study was a cross-sectional method with a purposive sampling technique with secondary data based on data obtained from the Puskesmas Parongpong and the research format consisting of the mother's socioeconomic status, namely income and education. The results of this study were: The highest education level of the mothers is in the middle, with the average number being 62,3%, it is categorized in Middle education. While the highest level of family income is in the middle, with the average number being 49%, it is categorized as Middle income. The evidence of stunted children under five years old is most categorized as short. Mothers are expected to pay more attention because mothers spend the most time with children and have to maintain the nutritional balance for their children during the growth and development period. As one of the health centers, Puskesmas Parongpong has to improve health promotion services about stunting and reduce the number of stunting events in their work area. Keywords : Stunting, Education, Maternal Income